E-marketing for Open Access Electronic Journal (Al-Mansour Journal, 2022)
This study aims to identified the importance of marketing in the field of Open Access Electronic Journals and indicate their Websites on the Internet, it is also discusses the importance of this sources as electronic information sources competitor to other electronic information. The study will includes proposal of a marketing plan for this type of electronic journals which composed the following elements:1- Develop a new product of electronic journals available in the standards ofscientific quality by: The value of Impact factor in specific field. The updating of articles information by measuring the journal Cited Half-Life.2- Development a good website which represent the fowling elements: Easy access to free electronic journals. Provide search capabilities and retrieval of information within a site ofperiodic. Access to the full text of articles.3- Determine the appropriate promotional tools available on the Internet toensure that increased demand for researchers to sites of these periodicals